Offset in a post-Brexit world - Matthews, Ron; Anicetti, Jonata (Taylor & Francis, 2021)
Prior to the launch of the European Procurement Directive, the UK’s erstwhile offset model was hailed a success. However, the directive compelled the UK to abandon its approach as the intention of the European Commission was to suppress and eventually remove offset from Europe’s defence-industrial landscape. Ron Matthews and Jonata Anicetti explain that Brexit has uncoupled UK defence procurement from the directive, creating the opportunity to reintroduce an industrial participation (IP) policy. Indeed, the Ministry of Defence has already taken the first tentative steps, as revealed in its March 2021 Defence and Security Industrial Strategy. This raises the question as to whether a ‘version 2.0’ IP policy will build on the original model’s success, and similarly reflect cooperation rather than coercion.